Analysis of Work Motivation and Leadership Techniques at Bank Sumedang - Sukmayadi Sukmayadi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The essence of the problem in this study is the closeness between the leadership and subordinates, the leadership does not give firm reprimands to its employees, employees feel less comfortable at work due to environmental factors and lack a leadership style in influencing their subordinates to work together. This study aims to determine employee motivation and to analyze the application of leadership techniques at Bank Sumedang. The types of data used are primary data and secondary data. Data collection methods are interviews and observation. The data analysis method used is descriptive method with qualitative data. The research results show that the motivation and leadership techniques at Bank Sumedang is fairly good. In the sense that the employees are very compact, solid, have a sense of kinship and always try and be responsible for their work and seen from the level of persistence, employees at Bank Sumedang are motivated by giving rewards and for the leadership style at Bank Sumedang it is considered good enough the way the leader prioritizes deliberation , make decisions and receive input that builds the organization in accordance with organizational goals. The conclusion that can be drawn is that by providing motivation and leadership techniques that is good and right for employees, it can motivate employees to work better in the future.